The first humans : The search for our origins - Thomas, Herbert (London : New Horizons, 1994)
Who are we? Where did we come from? What makes us human? The whole puzzle of our early life on earth is gradually being pieced together from fragments of bone, skulls and primitive tools dispersed throughout the world. The trail leads back nearly five million years. Here is a history of human evolution that reveals the very latest finds and thinking - discoveries that can help us to understand our past, our present and even future.
Keywords: Archaeology -- Non-fiction -- Evolution; Human Origins -- Science -- Prehistory